2010
DOI: 10.1007/s00572-010-0322-6
|View full text |Cite
|
Sign up to set email alerts
|

Soil–strain compatibility: the key to effective use of arbuscular mycorrhizal inoculants?

Abstract: Consistency of response to arbuscular mycorrhizal (AM) inoculation is required for efficient use of AM fungi in plant production. Here, we found that the response triggered in plants by an AM strain depends on the properties of the soil where it is introduced. Two data sets from 130 different experiments assessing the outcome of a total of 548 replicated single inoculation trials conducted either in soils with a history of (1) high input agriculture (HIA; 343 replicated trials) or (2) in more pristine soils fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 41 publications
0
25
0
2
Order By: Relevance
“…Despite the known benefits of plant mycorrhization, several conditions, such as soil type, fungus strain and host genotype, may limit association efficacy (Herrera-Peraza et al 2011). Therefore, specific research should be performed for each plantmycorrhiza symbiosis for successful crop development.…”
mentioning
confidence: 99%
“…Despite the known benefits of plant mycorrhization, several conditions, such as soil type, fungus strain and host genotype, may limit association efficacy (Herrera-Peraza et al 2011). Therefore, specific research should be performed for each plantmycorrhiza symbiosis for successful crop development.…”
mentioning
confidence: 99%
“…El origen volcánico del suelo implica la presencia de fósforo, pero este se encuentra entre un 54-90% inmovilizado por el aluminio y hierro no cristalinos, lo cual repercute en una escasa disponibilidad de este nutriente, constituyendo un serio limitante para el crecimiento de las plantas naturales y los cultivos (Geissert & Ibañez 2008, Codazzi 2009). La escasa movilidad y alta retención edáfica de este nutriente, acompañados de la condición ácida de la mayoría de los suelos han llevado al uso de diferentes estrategias para abastecer las demandas del cultivo, principalmente mediante el suministro de enmiendas orgánicas y/o quí-micas (Arcila et al 2007, Hernández-Martínez 2008 y la aplicación de hongos que forman micorriza arbuscular (Rodríguez 2001, Cardoso & Kuyper 2006, Herrera-Peraza et al 2011, pero en este cultivo no se ha implementado el uso de hongos solubilizadores de fosfatos.…”
unclassified
“…Herrera-Peraza et al (2011) suggested that inoculant production should consider the edaphic conditions in which the inoculant is applied, since the compatibility of the AMF isolate and mycorrhizal colonization can be modulated by soil type. Among the properties of the soil, pH interferes in germination, mycorrhizal colonization and formation of propagules.…”
Section: Water Availability and Sporulation Of Amfmentioning
confidence: 99%